(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is a fatal zoonotic disease, caused by the rabies virus, the prototype of the genus Lyssavirus of the Rhabdoviridae family, with a single-stranded negative- sense RNA genome, surrounded by a bullet shape capsid. In Venezuela for many years rabies has occurred in endemic and epidemic form, constituting a socioeconomic problem that affects human health and causes losses in livestock. It is distributed throughout the country. The detection of rabies antigen and antigenic characterization of field strains allowed the identification of animal species that serves as a reservoir responsible for an outbreak of rabies in a given area. The aim of this study was to perform the antigenic characterization of 34 fields isolates of rabies virus from different animal species, states and years, to know which antigenic variants were circulating in our country. The detection of rabies antigen was performed by direct immunofluorescence test of nerve tissue imprints of animals with symptoms of the disease. The viral amplification was performed by inoculation in suckling mice. Antigenic characterization was performed by indirect immunofluorescence impressions brains of mice inoculated with field strains that had obvious symptoms of the disease. Only variants 1 and 3 were found. It was concluded that the antigenic variant 1 (canine) was located exclusively in Zulia State, while variant 3 (vampire) was present in several states, so the common vampire bat D. rotundus was the main transmitter of rabies for livestock in that period.